Primary intracranial malignant melanoma in an adolescent girl with NRAS and TP53 mutations: case report and literature review - Liu, Xinyu; Shi, Hailiang; Wen, Xiaolong; Zhang, Kuo; Feng, Ge; Wei, Jie; Wang, Hebo (Frontiers in Oncology, 2024)
Primary intracranial malignant melanoma(PIMM) is often difficult to treat in patients without a history of skin melanoma or extensive melanin deposition. Due to the rarity of the disease, the current accepted treatment is surgical resection, but the prognosis is still poor. We report a case of PIMM in an adolescent girl with epilepsy as the only symptom and atypical imaging findings. PIMM was confirmed by further pathological and clinical examination. We summarize previous cases to discuss the clinical manifestations, imaging, pathological and genetic characteristics of the disease, aiming to improve the clinician’s understanding of the disease. This case underscores the PIMM as a differential diagnosis and prompt surgical treatment for adolescents with epileptic seizures accompanied by intracranial space-occupying lesions, even in the absence of extensive skin blackening.